Media Systems and Media Capture in Turkey: A Case Study - Murat Akser; Banu Baybars (Media and Communication, 2024)
This article attempts to explain the current situation of the Turkish media system through the media systems approach as a case study with special attention to the concept of media capture. We propose that the Turkish media system’s shift is heavily influenced by media capture. We associate four of Hallin and Mancini’s media systems concepts related to the effects of media capture in the Turkish media system shift: rise of political parallelism, erosion of journalistic professionalism (ethics), controlling role of the state, and government-friendly ownership concentration. In explaining the shift from a pluralist polarised to captured media in Turkey, we acknowledge the potential for new, independent, and alternative media to emerge. The article also comments that the potential reason for this shift from a captured liberal to a captured media in Turkey is the climate of fear that has allowed successive governments in Turkey to attempt media capture. In general, this article attempts to provide insight into the current relationship between media and politics in Turkey.